Hygroreceptionin Relation to Aggregation Behavior in Oniscus asellus - Dorschner, Ryan; Weiher, Evan R. (My University, 2017)
Oniscus asellus, the Common Shiny Woodlouse represent one of the only orders of terrestrial isopods that come from the crustacean family (Isopoda: Oniscidea). Woodlice elicit unique social behaviors in the form of aggregating with other individuals when subjected to changes in environmental conditions such as light intensity, temperature and relative humidity. This behavior is regarded as a method to prevent desiccation to which woodlice are extremely sensitive. Studying these isopods gives insight to the evolutionary mechanisms that allowed for terrestrial life as well as the development of basic social behaviors in response to fluctuations in environmental gradients. This research studied the effects of relative humidity with aggregation behavior of woodlice and hypothesized that humidity and aggregate formation have a causal relationship. Over 50 specimens of O. asellus were used during the experiment and were subjected to variations in humidity ranging from 30 – 90%. The rate at which aggregates formed and the cohesiveness of the aggregates were observed for each 10% difference in humidity. Results indicated that the rate and size of aggregation increased with rising humidity. At 70% humidity, woodlice formed aggregates fastest and remained in groups longest, while conditions that are more humid elicited less of a response.
Color poster with text, images, and graphs.
Keywords: Oniscus asellus; Ethology; Social behavior in animals; Isopods; Posters